Two case reports: EML4-ALK rearrangement large cell neuroendocrine carcinoma and literature review - Chen, Qin; Zhang, Jingjing; Wang, Xuan; Zong, Wenkang; Sun, Leina; Qin, Jianwen; Yin, Yan (Frontiers in Oncology, 2023)
We describe two rare metastatic large-cell neuroendocrine carcinoma (LCNEC) cases with an EML4-ALK arrangement, which demonstrateddemonstrating a rapid response to ALK-TKI inhibitors. Our review consolidates all pulmonary LCNEC cases with ALK mutations in the literature and concludes. It concludes that LCNEC patients with ALK mutations exhibit clinical features, such as a nonsmoking history, young age, and female sex, that are distinct from the general understanding of the disease. The majority ofMost patients can benefit from ALK inhibitors and achieve survival rates far exceeding those of conventional chemotherapy. These findings have implications for optimizing targeted therapy for specific subgroups of pulmonary LCNEC patients with ALK fusion. We recommend performing routine ALK IHC to identify potential candidates for ALK inhibitor treatments, particularly in young and nonsmoking women. This potential likely molecular testing algorithm may prove to be a valuable management approach, opening up promising therapeutic opportunities for specific subgroups in LCNEC.1. EML4-ALK+ Neuroendocrine lung cancer treated with ALK-TKI inhibitors showed a rapid response; 2. Large cell Neuroendocrine cancer patients with ALK fusion are mostly nonsmoking, young, and female; 3. Routine ALK IHC is recommended in advanced large-cell neuroendocrine cancer patients.